Persephone Ashton's Rite of Spring - Morris, Geraldine (Edinburgh: Edinburgh University Press, 2006)
RESUMEN: When Frederick Ashton began choreographing Persephone in 1961, he was regarded as the dominant British choreographer. He could, at this stage of his career, afford to take risks and choosing Persephone was undoubtedly risky. The ballet requires not only dancers but also a singer and chorus, and a leading dancer who can speak French verse. And, as Clive Barnes noted, it was unlikely ever to become a repertory work or achieve wide popularity. Ashton's Persephone was last performed in 1968, since when it has been ignored, the choreography has never been analysed in print before and the following exploration of the dances will, I hope, allow us to re-evaluate the work. By focusing on the inventive movement of these intriguing dances, I hope to show the vibrancy of his dance style and, despite the work having some uncharacteristic features, its relationship to other Ashton works.